Swimming against the tide: economic growth and demographic dividend in India. Issue 2 (4th May 2018) - Joe, William; Kumar, Abhishek; Rajpal, Sunil
ABSTRACT: There is an increasing policy focus on India's demographic potential and associated growth benefits. This paper provides empirical evidence regarding the net growth benefits derived from an increased share of working-age population in India. The analysis adopts decomposition and econometric methods, using data at the state and national level in India, to robustly test the nature and magnitude of the demographic dividend in India. We find that the Indian economy is drawing significant benefits from the ongoing process of demographic transition, with dividend effects estimated to be over one percentage point per annum during 1980–2010. However, to derive high growth from the demographic potential would require tackling some of the growth constraints. The paper discusses ways in which these constraints can be addressed to fully tap the potential of demographic dividend.